Could Concomitant Radio-Chemotherapy Improve the Outcomes of Early-Stage Node Negative Anal Canal Cancer Patients? A Retrospective Analysis of 122 Patients. (21st April 2015) - De Bari, Berardino; Lestrade, Laëtitia; Pommier, Pascal; Maddalo, Marta; Buglione, Michela; Magrini, Stefano Maria; Carrie, Christian
<x xml:space="preserve">Abstract</x> One hundred twenty-two early-stage anal canal cancer patients (median age: 69 years) were treated with curative radiotherapy with (70 patients) or without (52 patients) concomitant chemotherapy. Median follow-up was 65 months (range: 4–238). At multivariate analysis, concomitant chemotherapy significantly improved local control (p = .007). Local control significantly influenced all considered endpoints, except the metastases free survival. The global rates of G3–G4 acute and late toxicity were 13.1% and 8.2%, respectively, and they were not increased by concomitant chemotherapy. Finally, concomitant chemotherapy is efficacious and safe in the treatment of T1-2N0 anal canal cancer patients and should be prospectively studied.